Genetics of Depressive Disorders: Candidate Genes and Genome-Wide Association Studies - Rafikova, E. I.; Ryskov, A. P.; Vasilyev, V. A. (Russian journal of genetics, 2020)
The search for molecular genetic markers of depression has been going on for more than two decades, and it began with molecular studies of the genes of the neurotransmitter systems, primarily serotonin and dopamine. However, for most genes, the results of such studies remain contradictory. In the last decade, a new approach has been used to study the genetics of multifactorial diseases—a genome-wide search for associations. This method made it possible to supplement the list of potential genetic risk factors for depression with new genes that require additional research. The review describes two different approaches to the study of the genetics of depression, as well as current problems and recent advances in this field.